Comprehensive non-surgical treatment decreased the need for spine surgery in patients with spondylolisthesis: Three-year results - (:unkn) unknown (IOS PRESS, 2019)
BACKGROUND: Non-surgical treatment is the primary approach to degenerative conditions of the lumbar spine and may involve multiple modalities. There is little literature to guide an evidence-based approach to care. OBJECTIVE: To determine the effectiveness of CNT (comprehensive non-surgical treatment) in patients with degenerative spondylolisthesis (DS) and spondylolytic spondylolisthesis (SS), and to identify predictor variables for success of CNT in avoiding surgery. METHODS: All patients who underwent CNT for spondylolisthesis (n : 203) were included. CNT consisted of patient education, pain control with transforaminal epidural steroid injections (TFEs) and/or medications, and exercise programs. RESULTS: Surgical and non-surgical patients were similar in age, smoking status, comorbidity scores, facet joint widening, and translation of spondylolisthesis. After CNT, only 21.6% of patients with DS and 31.3% of patients with SS chose to have surgery in 3-years follow-up. The non-surgical group reported significantly better pain relief (73.6% vs 55%) after TFEs for a longer period (152.8 vs 45.6 days) and lower opioid use than the surgical group (28.2% vs 55.3%). CONCLUSIONS: CNT is effective in spondylolisthesis and more successful in DS than SS. CNT may decrease the need for surgery, particularly in patients who report pain relief greater than 70% for average five months after TFEs.
Keywords: Spondylolisthesis; back pain; epidural; steroids; non-surgical treatment; DEGENERATIVE LUMBAR SPONDYLOLISTHESIS; EPIDURAL STEROID INJECTIONS; LOW-BACK-PAIN; NONOPERATIVE TREATMENT; CONSERVATIVE MANAGEMENT; RADIOLOGIC-DIAGNOSIS; FOLLOW-UP; OUTCOMES; PREDICTORS; EXERCISE